ANALISIS PERBANDINGAN EMPLOYEE ENGAGEMENT GENERASI X DAN Y PADA DOSEN DAN TENAGA KEPENDIDIKAN DI IAIN SYEKH NURJATI CIREBON - Muhammad Qoes Atieq; Rezqi Ananda Basid (STIE Wiyatamandala, 2023)
A good higher education institution is an institution that is able to increase employee engagement, in various innovative ways so that lecturers and education staff feel valued and appreciated. Employee engagement in this study refers to the explanation of Schaufeli (2002) which is a motivational condition of employees related to work, which is indicated by enthusiasm, dedication, and absorption. The purpose of this study is to determine and explain the comparison of employee engagement on lecturers and education personnel of generations X and Y. This type of research is a comparative descriptive study with a quantitative approach. Collecting data using a questionnaire distributed online. The samples used were 150 people from various generations of respondents, namely 73 generations and 77 generations Y. Meanwhile, the data analysis used descriptive analysis, classical assumption test analysis, and independent sample t-test to compare. The results ofthe study indicate that there is a significant difference in the level of employee engagement of lecturers and education personnel of generations X and Y.